2021
DOI: 10.15252/embr.202153499
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone B specifically inhibits the NLRP3 inflammasome by disrupting NEK7‐NLRP3 interaction

Abstract: The activation of the nucleotide oligomerization domain (NOD)like receptor (NLR) family, pyrin domain-containing protein 3 (NLRP3) inflammasome is related to the pathogenesis of a wide range of inflammatory diseases, but drugs targeting the NLRP3 inflammasome are still scarce. In the present study, we demonstrated that Licochalcone B (LicoB), a main component of the traditional medicinal herb licorice, is a specific inhibitor of the NLRP3 inflammasome. LicoB inhibits the activation of the NLRP3 inflammasome in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 78 publications
0
28
0
Order By: Relevance
“…Compound 149-01, an analog of RRX001 without high-energy nitro functional groups, was recently identified as a potent and specific NLRP3 inhibitor that inhibits NLRP3 activation and attenuates inflammatory responses in vivo and vitro by preventing NLRP3 from binding to NEK7 ( 123 ). Licochalcone B (LicoB), a major component of traditional medicinal herb licorice, was also found to disturb the interaction between NLRP3 and NEK7, thus inhibiting NLRP3 activation ( 124 ). LL-Z1640-2(LLZ) is a preclinical drug that primarily targets TGF-β-activated kinase-1(TAK1), which produces a variety of proinflammatory cytokines and inflammatory mediators in RA.…”
Section: Potential Therapeutic Targets For the Nlrp3 Inflammasome In ...mentioning
confidence: 99%
“…Compound 149-01, an analog of RRX001 without high-energy nitro functional groups, was recently identified as a potent and specific NLRP3 inhibitor that inhibits NLRP3 activation and attenuates inflammatory responses in vivo and vitro by preventing NLRP3 from binding to NEK7 ( 123 ). Licochalcone B (LicoB), a major component of traditional medicinal herb licorice, was also found to disturb the interaction between NLRP3 and NEK7, thus inhibiting NLRP3 activation ( 124 ). LL-Z1640-2(LLZ) is a preclinical drug that primarily targets TGF-β-activated kinase-1(TAK1), which produces a variety of proinflammatory cytokines and inflammatory mediators in RA.…”
Section: Potential Therapeutic Targets For the Nlrp3 Inflammasome In ...mentioning
confidence: 99%
“… 14 , 37 Although the content of Lico B ( Figure 2B ) in Glycyrrhiza is relatively low, it has a strong anti-NLRP3 inflammasome effect. Our previous studies have shown that Lico B could specifically suppress NLRP3 inflammasome activation via binding to NEK7 and inhibiting the interaction between NLRP3 and NEK7 in BMDMs, THP-1 cells and human peripheral blood mononuclear cells (PBMCs) 38 ( Figure 3 ). In vivo experiments show that Lico B ameliorates LPS-induced septic shock characterized by improving survival rate, inhibiting IL-1β production, reducing the number of peritoneal exudative cells and peritoneal macrophages; Meanwhile, MSU-induced peritonitis, and methionine- and choline-deficient (MCD) diet-induced nonalcoholic steatohepatitis are significantly ameliorated by Lico B through targeting NLRP3 inflammasome.…”
Section: Pharmacological Inhibitors Of Nlrp3 Inflammasome In Glycyrrhizamentioning
confidence: 99%
“…In vivo experiments show that Lico B ameliorates LPS-induced septic shock characterized by improving survival rate, inhibiting IL-1β production, reducing the number of peritoneal exudative cells and peritoneal macrophages; Meanwhile, MSU-induced peritonitis, and methionine- and choline-deficient (MCD) diet-induced nonalcoholic steatohepatitis are significantly ameliorated by Lico B through targeting NLRP3 inflammasome. 38 Taking these studies into consideration, we firmly believe that with further investigation of its pharmacological effects will lead to Lico B becoming a promising candidate in the treatment of NLRP3-related diseases.…”
Section: Pharmacological Inhibitors Of Nlrp3 Inflammasome In Glycyrrhizamentioning
confidence: 99%
See 2 more Smart Citations